(untitled) (Scientific journal of the Fergana State University, 2025)
The article delves into the influence of internet neologisms on modern language, highlighting their emergence from online interactions and platforms like social media and forums. It explores their creative, and informal nature, including abbreviations and Internet-memes. These neologisms often encapsulate contemporary social phenomena. Their integration into mainstream language is driven by widespread usage, cultural relevance, and media endorsement, enriching vocabulary and fostering global communication. The research analyzes challenges whcih include potential instability in linguistic norms and generational divides in terms of understanding language norms. The article highlights that internet neologisms underscore language’s adaptability and dynamic evolution in the digital age.